Infectious Disease Outbreaks Act and Its Implication for Handling Corona Virus Spreading in Indonesia - Nariswari, Yasminna (Faculty of Law Universitas Negeri Semarang, 2020)
Health is a component of well-being because a healthy body is a key for self development. Health can be interpreted as an important investment to support economic development and has an important role in poverty alleviation efforts. Healthy lifestyle is what will safe us for short or long term benefits for ourself, it can reduce the risk of so many disease like cancer and another serious problem. Our body has its own immune to protect us from so many dangerous viruses, once a virus found a body which has a low immunity it will enter our body which will attack our immune system like for example cold and flu viruses. In the beginning of 2020 there is a new virus which first found in China, the virus called corona virus or covid-19 the virus spreads quickly from one person to another from one country to another and this situation becomes more serious as its number goes higher so quickly. This research is aims to analyze the infections diseas outbreaks Act and the implication on Covid-19 handling in Indonesia. This research compares some facts concerning Covid-19 policies in Indonesia to highlight the implication of policy and Act.